Age-associated changes in the content of collagen, elastin and glycosaminoglycans in rats’ skin and aorta - El-ta’alu, A.B.; Kot, Yu.G.; Falchenko, K.V.; Persky, Ye.E.; Ponomarenko, A.N. (V.N.Karazin Kharkov National University (Kharkov, Ukraine), 2008)
Age-related changes in concentrations of the major connective tissue macromolecules – collagen, elastin, separate fractions of glycosaminoglycans – hyaluronic acid, chondroitin sulphates, heparan sulphate, and dermatan sulphate, as well as their proportion in both the skin and aorta were studied. An age-related increase of collagen content in both the skin and aorta and at the same time a decrease of elastin content were shown in these tissues. The content of hyaluronic acid, chondroitin sulphates, heparan sulphate and dermatan sulphate increases in the skin with age. Contrarily, in the aorta, a decrease in concentrations of hyaluronic acid and dermatan sulphate takes place with age, while those of chondroitin sulphates and heparan sulphate increase.Исследовали возрастные изменения содержания основных макромолекул соединительной ткани – коллагена, эластина, а также отдельных фракций гликозаминогликанов – гиалуроновой кислоты, хондроитинсульфатов, гепарансульфата и дерматансульфата, и их соотношений в коже и аорте. Показано увеличение с возрастом содержания коллагена и уменьшение эластина в коже и аорте. Содержание гиалуроновой кислоты, гепарансульфата, хондроитинсульфата и дерматансульфата в коже увеличивается с возрастом. В аорте с возрастом наблюдается уменьшение концентрации гиалуроновой кислоты и дерматансульфата, в то время как концентрации хондроитинсульфатов и гепарансульфата увеличиваются.
Keywords: age; connective tissue; collagen; elastin; glycosaminoglycans